Gel Formulations of Guava Leaves (Psidium Guajava L) Leaves Ethanol Extract As a Wound Healing Of Burns in Rabbits - Sutrisno, Entris; Susilawati, Elis; Herdiana, Geralda Bintang; Noviyanti, Eva (Research Collaboration Community (Rescollacom), 2024)
The ethanol extract of guava leaves (Psidium guajava L) in previous studies was known to have antiburn, antiinflammatory, antidiarrhea and antibacterial activity. The preparations made are gel preparations which are preferred by the public. The purpose of this study was to determine the activity of guava leaf ethanol extract gel and its effective concentration in healing burns in rabbits. The research method uses rabbits 4 tails made 5 wounds on the back, consisting of negative control, comparison (Bioplacenton®), gel preparations 3%, 5%, and 11%. Wound diameter measurements were carried out on days 3, 6, 9, 12, 15 and 18. The parameters observed were the size of the wound diameter, wound healing such as wound drying, scab formation, closure of the wound and the growth of new hair around the wound. An inflammatory process occurs for 3 days after injury and not processed wound healing. Fibroblasts appeared on day 6 and peaked on day 9, so that on day 9 all treatment and control groups experienced linear healing. On the 9th day the fibroblasts began to peel off on the skin indicating the group has reached the peak of the proliferation phase and wound contractions occur gradually urgent. The results of the guava leaf extract gel activity test (Psidium guajava L) showed a concentration of 11% gave the best effect.